A new white-spotted moray eel, Gymnothorax aurocephalus sp. nov. (Muraenidae: Muraeninae) from Andaman Sea, India - Nashad, M.; Mohapatra, Anil; Varghese, Sijo P.; Ramalingam, L.; K, Bineesh K.; Mohanty, Swarup Ranjan (Zootaxa, 2020)
Gymnothorax aurocephalus sp. nov. is described herein based on 4 specimens. Three were collected from off Swaraj Dweep Island of Andaman and Nicobar Islands (A&N Islands) from a depth of 125–130 m and one specimen off Interview Island, A&N Islands at a depth of 90 m. This new species is distinguishable from its congeners by the following combination of characters: chocolate brown color overlain with small irregular white spots, golden skin shadings close to rictus; anus slightly before midbody; pointed and serrated jaw teeth; uniserial teeth in jaws and vomer; vertebral formula 7/61/148–149. The species is compared to all its congeners with white spots.